2016
DOI: 10.1016/j.plefa.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Peri-conception maternal lipid profiles predict pregnancy outcomes

Abstract: In this study, healthy women and those at high-risk of adverse pregnancy outcomes (pre-eclampsia, fetal growth restriction, gestational diabetes) were selected to assess the effect of fatty acid supplementation. The purpose of this paper is to report two novel findings (i) at recruitment the receiver operating characteristic (ROC) for erythrocyte oleic acid predicted spontaneous delivery at 34 weeks gestation (ROC=0.926 n=296) for all women entering the study. Further analysis revealed oleic and all monounsatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Since no established cutoff values exist for fatty acid status in pregnant women, erythrocyte fatty acid concentrations were compared to the reference values provided by the laboratory and to those of the few studies which reported maternal erythrocyte fatty acid levels early in the pregnancy [ 39 , 47 49 ]. Overall, Belgian pregnant women exhibited similar mean fatty acid concentrations, except for myristic acid and the three measured MUFA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since no established cutoff values exist for fatty acid status in pregnant women, erythrocyte fatty acid concentrations were compared to the reference values provided by the laboratory and to those of the few studies which reported maternal erythrocyte fatty acid levels early in the pregnancy [ 39 , 47 49 ]. Overall, Belgian pregnant women exhibited similar mean fatty acid concentrations, except for myristic acid and the three measured MUFA.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies investigated the relationships between erythrocyte MUFA during first trimester of pregnancy and birth outcomes. While one have observed that oleic acid and MUFA predicted low birthweight [ 49 ], the other found no association between MUFA and birth outcome measures (birth weight, birth length, head circumference and chest circumference at birth) [ 51 ]. It is worth noting that mean MUFA levels of the second study were similar to those of our study, in contrast to the first which were higher.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body compensates for low PUFA (ω‐3 and ω‐6) levels by increasing the endogenous production of oleic acids (MUFAs) to ensure that the composition and function of the cell membrane remain normal (Ogundipe, Johnson, Wang, & Crawford, ). Jones et al () found that oleic acid levels are low in pregnant women with fetuses with gastroschisis, similar to the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Seafood studies more likely reflect habitual diets 5 [34]. Consumption prior to conception may be important for neurocognitive development [35]. Nonetheless, results of the omega-3 supplementation RCTs during pregnancy at least raise the possibility that the beneficial effects seen in the seafood studies are not solely attributable to omega-3 fatty acids.…”
Section: Considerations About Benefitsmentioning
confidence: 99%